1991
DOI: 10.1111/j.1528-1157.1991.tb05613.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Occipital Epileptiform Activity: Is It Benign?

Abstract: Occipital epileptiform activity that is almost continuous and reactive to eye opening has been associated with a childhood epilepsy syndrome and basilar migraine with seizures. An association of these syndromes with a benign course had been disputed. In this study, a retrospective investigation of reactive occipital epileptiform activity (ROEA) was performed to determine the prognostic value of this distinctive EGG pattern. The EEG and hospital record of patients with ROEA were reviewed with an observation per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 9 publications
1
14
0
2
Order By: Relevance
“…Эти пароксизмы устраняются или заметно уменьшаются, когда глаза открыты [25,32,33]. Это яв-ление считается патогномоничным для синдрома Гасто, однако имеются сообщения о возникновении данного феномена у пациентов с синдромом Панайотопулоса и с другими формами эпилепсии [6,23].…”
Section: том х делов левой височной области с признаками атрофии висоunclassified
See 1 more Smart Citation
“…Эти пароксизмы устраняются или заметно уменьшаются, когда глаза открыты [25,32,33]. Это яв-ление считается патогномоничным для синдрома Гасто, однако имеются сообщения о возникновении данного феномена у пациентов с синдромом Панайотопулоса и с другими формами эпилепсии [6,23].…”
Section: том х делов левой височной области с признаками атрофии висоunclassified
“…На ЭЭГ могут отмечаться затылочные спайки и волны, исчезающие после от-крывания глаз, что характерно для детской затылоч-ной эпилепсии типа Гасто и может отмечаться при синдроме Панайотопулоса [6,23].…”
Section: дифференциально-диагностические признаки синдромов панайотопunclassified
“…Studies based on EEG selection criteria showed that CEOP accounted for 6-72% of the cases (11,(43)(44)(45)(46). Moreover, some patients may have EEG findings without a clinical seizure (11,42,44,45,47,48). Thus, it is important to stress that the diagnostic criteria for CEOP should be based on the finding of occipital spikes on the EEG and a clinical seizure in the absence of neurological deficit or neuroradiological evidence of brain damage, although the EEG findings may not always present in the interictal EEG of patients with CEOP (1,9,13,14,38,49).…”
Section: Figmentioning
confidence: 99%
“…The presence of occipital spike waves suppressed by eye opening, one of the criteria in the first report of Gastaut (1), is associated with a wide range of clinical disorders, including lesional epilepsy and learning disabilities (41,42). Studies based on EEG selection criteria showed that CEOP accounted for 6-72% of the cases (11,(43)(44)(45)(46).…”
Section: Figmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] Panayiotopoulos-type benign childhood occipital epilepsy (Panayiotopoulos-type CEOP), as we have proposed to name 12,14 the entity-which currently is being considered for inclusion in a revised classification of epileptic syndromes and diseases by the ILAE 2,17 -has uniform clinical and EEG features and excellent prognosis. The syndrome may be underdiagnosed in the United States, as indicated in recent reports, [18][19][20] or misdiagnosed as encephalitis, other serious brain insults, or migraine. The seizures mainly consist of ictal vomiting and deviation of the eyes, often with impairment of consciousness and progression to convulsions.…”
mentioning
confidence: 99%